Small and medium-sized enterprises financing / Ibrahim Nandom Yakubu, Abdul-Majeed Sulemana and Iliasu Abdallah - Yakubu, Ibrahim Nandom; Sulemana, Abdul-Majeed; Abdallah, Iliasu (Universiti Teknologi MARA Cawangan Pahang, 2020)
The operations of small and medium-sized enterprises (SMEs) occupy an admirable position in the economic landscape of most economies in the world, especially for developing countries. Based on literature review, this paper critically assesses the sources of finance available to SMEs and the difficulties they encounter in accessing these finances. The study identified bank loans, venture capital financing, business angels, trade credit, and government support as the key sources of finance available to SMEs. The study further shows that limited resources, personal characteristics of SMEs managers, and the nature of some SMEs are the common factors inhibiting SMEs access to finance